Evaluasi Mutu Beras dalam Penentuan Pola Preferensi Konsumen terhadap Beras di Pulau Jawa - Mardiah, Zahara; Rakhmi, Ami Teja; Indrasari, Siti Dewi; Kusbiantoro, Bram (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Java is the most populated areas as well as the highest consumers of rice in Indonesia. Until now, rice which is widely consumed by the population of Java Island is still dominated by Ciherang, while planting the same varieties in long period time will cause ... This research aims to study the patterns of consumer preferences in Java on rice as one of the considerations for dissemination and assembly of new varieties. Evaluation is done by conducting sensory and physicochemical analysis on the five most widely purchased rice of each province on Java island. Hedonic and ranking test was assessed by 1000 panelists that were scattered in five provinces in Java. While the physicochemical analysis carried out in the Proximate Laboratory in Indonesian Center for Rice Research (ICRR), Sukamandi. In general, consumer preferences in each province in Java has a similar pattern except in DIY. Consumers in Java prefers rice with intermediate amylose content except those in DIY who like low amylose rice. Gelatinization temperature of rice is mostly high gelatinization temperature except those in DIY that dominated by low gelatinization temperature rice. Moreover, rice color influences consumer preferences in Java except on consumers in the West Java who chose the rice was not based on the level of rice white color.